Programma: 2-4 april Piro; 8-10 april The Creative Dance Theatre; 15-17 april Graziella Martinez; 16-18 april British Theatre Group; 23-25 april Window; 22-24 april Graziella Martinez (1976)
Programma: 2-4 april Piro; 8-10 april The Creative Dance Theatre; 15-17 april Graziella Martinez; 16-18 april British Theatre Group; 23-25 april Window; 22-24 april Graziella Martinez.